Variants of kulintangan performance as a major influence of musical identity among the Sama in Tawitawi, Philippines - Ellorin, Bernard B. (University Microfilms, 2008)
In this thesis, emphasize how a Philippine ethno-linguistic group's diversity can be seen through music found within its sub-groups. Using margaret kartomi's theory of traditional and contemporary musical conservation, I also argue that these musicians conserve their sub-group's style of kulintangan music as an iconic musical tradition that contributes to the Sama regional identity in Tawitawi.